2022
DOI: 10.1039/d2tc03202c
|View full text |Cite
|
Sign up to set email alerts
|

Structure-related bandgap of hybrid lead halide perovskites and close-packed APbX3 family of phases

Abstract: Metal halide perovskites APbX3 (A+ = FA+ (formamidinium), MA+ (methylammonium) or Cs+, X- = I-, Br-) are considered as prominent innovative components in nowadays perovskite solar cells. Crystallization of these...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…In previous work, IPA was employed to enhance the crystallinity of MAPbI 3 films [23]. However, in FA-based perovskite, it was found that IPA could trigger the undesirable α-to-δ phase transition, which increases the pristine material's bandgap and lowing the charge carrier mobility [34], resulting in deteriorated device PCE. The IPCE curves for these PSCs were also measured (Figure 5b), where CB-and DMF-treated samples exhibited the highest and lowest current, respectively, corresponding well to the JV results.…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, IPA was employed to enhance the crystallinity of MAPbI 3 films [23]. However, in FA-based perovskite, it was found that IPA could trigger the undesirable α-to-δ phase transition, which increases the pristine material's bandgap and lowing the charge carrier mobility [34], resulting in deteriorated device PCE. The IPCE curves for these PSCs were also measured (Figure 5b), where CB-and DMF-treated samples exhibited the highest and lowest current, respectively, corresponding well to the JV results.…”
Section: Resultsmentioning
confidence: 99%
“…Since crystallization of perovskites is often complicated, and the formation of various phases with the same stoichiometry is inevitable, the presence of such polytypes in the perovskite matrix is responsible for a decrease in the mobility of charge carriers. 49 The change of the divalent metal and anionic components change the X−B−X bond impact and tune the bandgap of a metal halide perovskite. 32,50 By substitution of larger cations such as FA and MA, the lattice of metal halide perovskite expands, and the bandgap decreases.…”
Section: Fundamentals Of Perovskites: Crystal Structures Different Ph...mentioning
confidence: 99%
“…It was reported that there is a nonlinear relationship between the band gap and the ratio of cubic and hexagonal layers in these structures. Since crystallization of perovskites is often complicated, and the formation of various phases with the same stoichiometry is inevitable, the presence of such polytypes in the perovskite matrix is responsible for a decrease in the mobility of charge carriers …”
Section: Fundamentals Of Perovskites: Crystal Structures Different Ph...mentioning
confidence: 99%
“…has cost mankind in terms of cost effectiveness and less availability. Therefore, there is a need for the replacement of these materials by easily available and lab synthesized low cost materials that do no compromise their performance. , The lead perovskites (PbXO 3 , X = Ti, Zr, Hf) fit in this category due to the presence of s - p hybridization between the O and Pb atoms forming the polyhedra which offers diverse functionality to integrate in different applications such as optoelectronic, thermoelectric devices, sensors, etc. In our survey, we have found that limited experimental work has been carried out owing to the lead toxicity. Earlier studies have reported that pristine lead perovskites have exhibited ferroelectric behavior. It is well-known that the Pb-based perovskite systems exist in two or more structural phases, viz , tetragonal (low temperature) and cubic (high temperature).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need for the replacement of these materials by easily available and lab synthesized low cost materials that do no compromise their performance. 10,11 The lead perovskites (PbXO 3 , X = Ti, Zr, Hf) fit in this category due to the presence of s-p hybridization between the O and Pb atoms forming the polyhedra which offers diverse functionality to integrate in different applications such as optoelectronic, thermoelectric devices, sensors, etc. 12−17 In our survey, we have found that limited experimental work has been carried out owing to the lead toxicity.…”
Section: ■ Introductionmentioning
confidence: 99%